2006
DOI: 10.1038/nature04921
|View full text |Cite
|
Sign up to set email alerts
|

A ubiquitous thermoacidophilic archaeon from deep-sea hydrothermal vents

Abstract: Deep-sea hydrothermal vents play an important role in global biogeochemicalcycles, providing biological oases at the seafloor that are supported by the thermal and chemical flux from the Earth's interior. As hot, acidic and reduced hydrothermal fluids mix with cold, alkaline and oxygenated seawater, minerals precipitate to form porous sulphide-sulphate deposits. These structures provide microhabitats for a diversity of prokaryotes that exploit the geochemical and physical gradients in this dynamic ecosystem 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
189
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(194 citation statements)
references
References 27 publications
(9 reference statements)
5
189
0
Order By: Relevance
“…From the 10 euryarchaeotal genomic clones sequenced, 3 were ascribed to the Group III and the rest to deep-sea Group II members, as none of the 16S rDNA sequences from our libraries branched with the phototrophic euryarchaeota Comparative metagenomics of deep-sea archaea A-B Martin-Cuadrado et al . The recently isolated Aciduliprofundum boonei, an obligate thermoacidophilic sulphur-or iron-reducing heterotrophic deep-sea vent archaeon representative of the DHVE2 group (Reysenbach et al, 2006), branched closer to the Thermoplasmatales than to the Groups II and III ( Figure 3 and data not shown). As in the case of crenarchaeota, we sequenced fosmids from the same pan-oceanic OTUs coming from at least one Mediterranean and one South Atlantic or Antarctic location.…”
Section: Archaeal Fosmids In Deep-sea Metagenomic Librariesmentioning
confidence: 99%
“…From the 10 euryarchaeotal genomic clones sequenced, 3 were ascribed to the Group III and the rest to deep-sea Group II members, as none of the 16S rDNA sequences from our libraries branched with the phototrophic euryarchaeota Comparative metagenomics of deep-sea archaea A-B Martin-Cuadrado et al . The recently isolated Aciduliprofundum boonei, an obligate thermoacidophilic sulphur-or iron-reducing heterotrophic deep-sea vent archaeon representative of the DHVE2 group (Reysenbach et al, 2006), branched closer to the Thermoplasmatales than to the Groups II and III ( Figure 3 and data not shown). As in the case of crenarchaeota, we sequenced fosmids from the same pan-oceanic OTUs coming from at least one Mediterranean and one South Atlantic or Antarctic location.…”
Section: Archaeal Fosmids In Deep-sea Metagenomic Librariesmentioning
confidence: 99%
“…These systems have yielded a rich variety of novel chemolithotrophs 1,9,15,57,65,76,77,79,87) capable of exploiting the typically high concentrations of reduced inorganic substrates (especially various sulfur species) associated with many volcanic environments. The properties of many of these isolates have been unexpected, and opened new horizons in microbial biology 35,39,70,84) .…”
Section: B Chemolithotrophy and Reductant-rich Volcanic Systemsmentioning
confidence: 99%
“…MG2-GG3, similar to many other marine prokaryotes, seems to be a photoheterotroph, possessing a rhodopsin to collect light energy but with the hallmarks of a heterotrophic lifestyle. The existence of many large peptidases, similar to the ubiquitous thermoacidophilic archaeon Aciduliprofundum boonei, a known protein degrader from deep-sea hydrothermal vents (Reysenbach et al, 2006), suggested that proteins may be important substrates for this microbe. Moreover, the presence of a complete fatty acid degradation pathway, together with proteins with a variety of adhesion domains and a type II/IV secretion systems to transport such proteins to the cell surface, led the authors to suggest a particle-associated lifestyle.…”
Section: Introductionmentioning
confidence: 99%